Plyometric and strength training of speed test in hockey players / Nur Ain Zareen Mohamad Noor Asmadi - Mohamad Noor Asmadi, Nur Ain Zareen (Faculty of Sport Science and Recreation, 2016)
Cronin and Hansen (2005) for many sporting activities, initial speed rather than maximal speed would be considered of greater importance successful performance. The purpose of this study was to identify the best training regime to enhance speed performance. The subjects were randomly separate into two groups which is plyometric group (N=12) and strength group (N=12). Both of the groups were performed the exercise within two times per week lasting eight weeks. The results of paired sample T-Test shown at the Sig. (2-tailed) which stated that 30-meter dash for plyometric (p=0.134), and strength (p=0.193). It shown that p>0.05 and also stated that there is no significant between both training. For 60-meter dash for plyometric (p=0.260), it also stated that there no significant while for strength (p=0.085), it shown that p<0.05 and also stated that there is a significant effect of plyometric and strength training of speed test among hockey players. This are been shown that 60-meter strength training have a significant effects on speed test in hockey players.